Body size estimation of Caimaninae specimens from the Miocene of South America. (October 2022) - Paiva, Ana Laura S.; Godoy, Pedro L.; Souza, Ray B.B.; Klein, Wilfried; Hsiou, Annie S.
Abstract: Living crocodylians are frequently regarded as morphologically and ecologically conservative, contrasting with the group's rich fossil record, which reveals a much higher diversity. In particular, Caimaninae is a striking example of such diversity, with only six extant species but a myriad of extinct taxa, exhibiting remarkable morphological variation. Their skulls vary substantially, with robust and flattened shapes, ranging from short to long snouts, and serve as a basis for many evolutionary studies in the group. Previous works have demonstrated that the skull is a good proxy to estimate the body size of extinct crocodylians. In this study, we estimate the body size of large Caimaninae specimens from the Miocene of South America, including Purussaurus and Mourasuchus . For that, we elaborated a comprehensive dataset of body size data collected from living crocodylians to generate regression equations. We performed regression analyses both including and excluding juvenile/subadult specimens, to account for the possible influence of ontogeny on the relationship between cranial measurements and body size. Furthermore, we also employed two different approaches (phylogenetic and non-phylogenetic) for estimating the body size of these Miocene caimanines. Our results indicate a significant influence of ontogeny on the body proportions of crocodylians, suggesting that datasets used for estimating the body size of extinct taxa should not include juvenile specimens. Moreover, the phylogenetic approach provided more conservative estimates, possibly as a result of the phylogenetic position of the analyzed taxa, given that the body size metrics are strongly phylogenetically structured in crocodylians. This is the first study to infer the body size of fossil caimanines using different methods and skeletal measurements, as well as a dataset comprised of solely adult crocodylians. In the light of our results, we also discuss the paleobiological implications of the large size of these Miocene caimanines. Highlights: Body proportions of crocodylians vary during ontogeny. Juveniles should not be used to estimate the body size of extinct crocodylians. Phylogenetic approach provides more conservative body size estimates. Dorsal cranial length is less robust than skull width as a proxy for body size.